Cellular fluorescein hyperfluorescence is dynamin-dependent and increased by Tetronic 1107 treatment. (August 2018) - Khan, Tahmina F.; Price, Bianca L.; Morgan, Philip B.; Maldonado-Codina, Carole; Dobson, Curtis B.
Highlights: Clinical solution-induced corneal staining can be reproduced in an in vitro model. Increased fluorescein uptake does not correlate with necrotic or apoptotic cells. Dynasore, an inhibitor of dynamin, reduces cellular uptake of fluorescein. Surfactant Tetronic 1107 increases fluorescein uptake whereas Triton X-100 does not. Abstract: Sodium fluorescein ('fluorescein') staining of the ocular surface is frequently an indicator of compromised ocular health, and increases in the presence of certain contact lens multi-purpose solutions (MPS), a phenomenon known as solution induced corneal staining (SICS). The mechanism(s) underpinning fluorescein hyperfluorescence are uncertain, though may reflect increased cellular uptake of fluorescein by corneal epithelial cells. We have developed an in vitro model to study fluorescein uptake in both 'generic' mammalian cells (murine fibroblasts) and human corneal cells. Fluorescein hyperfluorescence increased after treatment with two MPS associated with clinical corneal fluorescein staining, yet there was no cellular hyperfluorescence for two MPS that do not cause this staining. Increased fluorescein uptake did not correlate with presence of a necrotic or an apoptotic marker (propidium iodide and caspase-3 respectively). Incubation of MPS-treated cells with dynasore (an inhibitor of dynamin, implicated in endocytic pathways) reduced fluorescein uptake irrespective of MPS treatment. The non-ionic surfactant Tetronic 1107 (present in both MPS associated with corneal fluorescein staining) increased uptake of fluorescein for both cell types, whereas an unrelated surfactant (Triton X-100) did not. We conclude that the clinical hyperfluorescence profile observed after exposure to four MPS can be reproduced using a simple model of cellular fluorescein uptake, suggesting this is the biological basis for SICS. Fluorescein entry does not correlate with necrosis or apoptosis, but instead involves a dynamin-dependent active process. Moreover the surfactant Tetronic 1107 appears to be a key MPS constituent triggering increased fluorescein entry, and may be the major factor responsible for SICS.